PERANAN DESA ADAT DALAM PENANGANAN PANDEMI COVID-19 DI DESA DALUNG KECAMATAN KUTA UTARA KABUPATEN BADUNG PROVINSI BALI - Bhakti, I Gede Umbu; Artadi, I Putu Hardi Surya; Budiman, La Arif (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This research was based on the increasment of the positive cases of COVID-19 which is absolutely huge cases. This afected towards the villagers economic which is the task of the traditional village in controlling, efforting, and serving the implementation of Parahyangan, Pawongan and Palemahan in Traditional Village therefore the role of the traditional village is exactly needed to conserve the Covid-19 Pandemic. This research aimed to know the role of traditional village in conserving the Covid-19 pandemic, also knowing the factors which are able to decrease the Pandemic case of Covid-19 and the effort that the traditional village to be done in conserving the Pandemic of Covid-19 at Dalung Village North Kuta District Badung Regency Bali Province. Normatively, this research refers to Bali Provincial Regulation Number 4 of 2019 about Traditional Village in Bali and teoritically this research refers to synergy theory by Stephen R. Covey. This research was qualitative using descriptive method and inductive approach. The technique of data gathered through interview, observation, and documentation. The technique of data analyzis was through data gathered, data reduction, data display, and conclusion drawing. The result of this research showed that the role of the traditional village in conserving the Pandemic of Covid-19 is already optimal which is showed by the amount case of Covid-19 has decreased, even though the obstacle is stil exist such as the people still disobey the health protocol, but this has been followed up by pecalang and giving sanctions for those who violate the Covid-19 health protocol.